Advances in magnetic resonance in food science - Belton, P. S.; Hills, B. P.; Webb, G. A., 1935-; ScienceDirect eBooks; International Conference on Applications of Magnetic Resonance in Food Science 07-09-1998 - 09-09-1998 : Norwich, England) (Cambridge : Royal Society of Chemistry ; Cambridge : Woodhead Publishing, 1999)
The highly versatile nature of magnetic resonance techniques in dealing with problems arising in many areas in food science is demonstrated in this book. Topics covered include development of the technique, functional constituents of food, signal treatment and analysis, along with applications of magnetic resonance to food processing and engineering. The international flavour of the contributions to this text aim to make it of value to both academics and industrialists in food science.
Chapter 8. Probing the Physical and Sensory Properties of Food Systems Using NMR Spectroscopy1 INTRODUCTION; 2 SELECTING A TECHNIQUE TO PROBE COMPLEX FOOD MATERIALS; 3 PROBING THE PHYSICAL AND SENSORY PROPERTIES OF FOOD MATERIALS USING NMR SPECTROSCOPY; 4 PROBING PHYSICAL PROPERTIES -- AN EXAMPLE; 5 PROBING SENSORY PROPERTIES -- AN EXAMPLE; 6 SUMMARY; 7 ACKNOWLEDGEMENTS; References; Chapter 9. 1H Relaxation of Hydrated Carbohydrate Systems; ABSTRACT; INTRODUCTION; EXPERIMENTAL PROCEDURES; DECAY SHAPES; A BEAT IN THE FID; WATER RICH SAMPLES; LOW WATER CONTENT SAMPLES; REAL FOODS; CONCLUSIONS.
The proceedings of the Fourth International Conference on Applications of Magnetic Resonance in Food Science, held on 7-9 September 1998 in Norwich, UK.
With bibliographical references and index.
Elsevier
Keywords: Food -- Analysis -- Congresses; Magnetic resonance imaging -- Congresses; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Analysis; Magnetic resonance imaging; Electronic books